A study to evaluate the effectiveness of a structured teaching program on breast self-examination among adult women in a selected rural area of Visnagar, Gujarat - Patel Jinal Ashvinkumar, N.Siva Subramanian, Patel Kaxkumar Vasantbhai,Patel Krimi Pravinkumar, Patel karinaben kamleshbhai,Patel krupa Bharat bhai,Patel Kevin Dilipkumar; Patel kinnari Bhaveshbhai, Vaghela Payalben Tejmalji , Chaudhari Ankitaben Bhagavanbhai (South Eastern European Journal of Public Health, 2025)
Background: Breast cancer continues to be an important public health issue, and early detection using breast self-examination (BSE) helps decrease mortality rates. In spite of its utility, awareness and practice of BSE among youth are low. This research investigated the effectiveness of a structured educational program in enhancing knowledge about BSE among adolescent girls in Visnagar. Methods: A pre-test and post-test quasi-experimental research design was utilized, with 50 adolescent girls recruited by purposive sampling. A structured knowledge questionnaire was used to collect the data prior to and subsequent to the delivery of the teaching program. Descriptive and inferential statistical analyses were undertaken and a paired t-test was applied for determining the significance of the intervention. Results: The results indicated that pre-test knowledge was poor among most participants (41.7%). But, post-intervention, 66.7% of the participants showed good knowledge. The mean post-test (16.9) was markedly greater than pre-test (10.06) with a value of paired t-test 40.12 (p < 0.001). No correlation between demographic characteristics and levels of knowledge was significant, except information sources, which significantly affected. Conclusion: The research highlights the efficacy of systematic educational interventions in promoting knowledge and awareness of BSE. Incorporating such programs into community health programs can have a significant impact on early detection practices, leading to improved health outcomes